2013
DOI: 10.1530/jme-12-0154
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between EGR1 and SP1 is critical for 13-cis retinoic acid-mediated transcriptional repression of angiotensin type 1A receptor

Abstract: Recently, we have demonstrated that 13-cis retinoic acid (13cRA) down-regulates rat angiotensin type 1A receptor (AT1AR) gene transcription through a MAP Kinase (ERK1/2) dependent mechanism in rat liver epithelial and aortic smooth muscle cells. However, the exact mechanism remained unknown. In this study, we determined the signaling intermediates activated by ERK1/2 involved in 13cRA mediated AT1AR down-regulation. Serially deleted rat AT1AR promoter CAT constructs indicate fragments containing a region −2541… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Several of the EGR1 downstream target genes have multiple overlapping SP1 and EGR1 binding sites in their proximal promoter regions. The regulatory relationship in this overlapping area is complex, in some genes the two factors are synergistic, and antagonistic in others ( 70 , 92 , 93 ). The duality of EGR1 is related to the regulatory relationship between the two factors.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the EGR1 downstream target genes have multiple overlapping SP1 and EGR1 binding sites in their proximal promoter regions. The regulatory relationship in this overlapping area is complex, in some genes the two factors are synergistic, and antagonistic in others ( 70 , 92 , 93 ). The duality of EGR1 is related to the regulatory relationship between the two factors.…”
Section: Discussionmentioning
confidence: 99%
“…Similar Sp1/Egr-1 overlapping binding sites have been shown to play a critical role in the expression of some genes, such as TF , NDRG1 and PDGF-A [ 14 - 16 ]. The regulation of transcription by these two transcription factors has been shown to be complex: in some genes the two factors are synergistic, whereas in other systems the factors appear to compete [ 17 , 18 ]. Egr-1 encodes a nuclear phosphoprotein that binds to the GC-rich sequence 5'-GCGGGGGCG-3' and regulates transcription of target gene through the GC-rich consensus sequence [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This process leads to activation of ATRA-responsive genes via alteration of chromatin structure and enables cellular differentiation of normal myelomonocytic progenitor cells [33]. Compared with the endogenously formed isoforms ATRA and 9-cis RA, 13-cis RA has relatively weak transactivation activity for RAR/RXR, and it may possess a novel signaling pathway of its own [34]. It has reported that ATRA could be, at least partially, converted into 9-cis RA and 13-cis RA in vitro, but 9-cis RA and 13-cis RA may produce biological effects distinct from those produced by ATRA [35].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that 13-cis RA can act as a potent inhibitor of many of the retinoid and hydroxysteroid mediated pathways [36]. A recent research showed that 13-cis RA mediated activation of ERK1/2, is capable of disrupting transcription factor Sp1, the requisite transactivator for angiotensin type 1A receptor (AT1AR) gene transcription, leading to an inhibition on AT1AR expression [34]. Besides, in our study, we only focused on transcription factor CREB, we could not rule out whether RA or RAR may in conjunction with other transcription factors such as SP1/3 and modulate ORMDL3 expression.…”
Section: Discussionmentioning
confidence: 99%